Anatomical Responses of Ajwa Dates Sprouts (Phoenix dactylifera L.) to Water Availability and light Intensity - Triastari Armanda, Dian (Journal Of Natural Sciences And Mathematics Research, 2015)
As the biggest Moslem population in the world, Indonesia still has a high dependency on importing date palms from other countries. Ajwa dates (Phoenix dactylifera L.) is one of special date palm cultivar which had cultivated since 5000 BC in arid climate area in Saudi Arabia. Adaptation and optimation of environmental factors for Ajwa dates cultivation in Indonesia are important to be conducted to meet the date palm demand of this country. A study on anatomical responses of Ajwa dates sprouts to water availability and light intensity has been conducted. Ajwa date sprouts had been exposed to combinations of three shade variations (0%, 50%, and 90% shade) and four water availability variations (25%, 50%, 75%, and 100% of the field capacity).Â  Data were taken from day 0 until day 45 of germination. Morphological parameters which observed and analyzed were the leaf blade length and sprouts root length. Anatomical parameters which observed and analyzed were root radius, stele diameter, leaves numbers, leaves thickness, and stomatal diameter. Variations on water availability and light intensity gave the same effect (not significantly different) in almost every parameters which measured, therefore, the most optimal combination water-light treatment was still unknown. Advanced research and longer duration of experiment need to be conducted to gain the complete information regarding the optimization of environmental factors to increase the Ajwa date productivity in Indonesia.